A molecular and morphological phylogeny of the extant Augochlorini (Hymenoptera, Apoidea) with comments on implications for biogeography. (18th January 2016) - GONÇALVES, RODRIGO B.
Abstract: The Augochlorini Beebe is a New World tribe of bees comprising 663 described species. Relationships among the genera of this monophyletic tribe remain uncertain. Here I provide a comprehensive phylogeny using morphological and molecular information. In all, 54 Augochlorini species plus 16 outgroups and 3017 molecular and 105 morphological characters were analysed. Sequences for four genes were analysed using Bayesian inference, maximum likelihood and parsimony. Morphological characters were taken from a literature review and analysed alone and in combination with molecular data using parsimony. The monophyly of Augochlorini and most genera is confirmed, with divergence of the main lineages of the tribe around 55–20 Ma. Seven clades were supported by most analyses and are here treated as genus‐level groups, as follows (combined analysis topology): ( Corynura group, ( Chlerogella group, (Rhinocorynura group, ( Augochloropsis, (Megaloptidia group, (Neocorynura group, (Augochlora group, Megalopta group))))))). According to this topology, dim‐light foraging and cleptoparasitism arose three times in the tribe. According to my hypothesis, the diversification of Augochlorini may have begun as a response to vicariant events, including the split of the Neotropical/Andean regions and marine transgressions in the Amazon region.